The Influence of Electronic Payment Usage, Lifestyle, and Financial Literacy on the Consumptive Behavior of Santri: A Case Study at PPSM Thohir Yasin, East Lombok - Triwibowo, Bambang; Yusup, Muhamad; Mulhimmah, Baiq Ratna (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2025)
Islamic boarding schools (pesantren), as traditional centers of Islamic education, are increasingly confronted with the challenges posed by modernization, particularly in the domain of financial technology. In response, PPSM Thohir Yasin implemented an electronic payment system utilizing smart card technology through its affiliated business unit, Thohir Yasin Mart. This study aimed to examine the influence of electronic payment, lifestyle, and financial literacy on the consumptive behavior of Madrasah Aliyah (MA) students at PPSM Thohir Yasin. Employing a quantitative research design with a cross-sectional survey method, data were collected from 300 students selected through stratified purposive sampling based on class level, gender, and residential status. Structured, closed-ended questionnaires were disseminated online during the pesantren’s Ramadan holiday in 2025. Data analysis was conducted using SPSS version 25, incorporating validity and reliability testing, classical assumption checks, and multiple linear regression analysis. The results indicated that electronic payment exerted a negative and significant influence on consumptive behavior (t = -8.760; p < 0.001), lifestyle demonstrated a positive and significant impact (t = 5.719; p < 0.001), while financial literacy had a positive but statistically non-significant effect (t = 1.682; p = 0.094). Collectively, the three variables significantly influenced consumptive behavior (p < 0.001), explaining 29.8% of the variance (R² = 0.298). The study concludes that lifestyle is the most influential factor driving students’ consumptive behavior, whereas financial literacy does not yet exert a substantial effect. These findings underscore the need for pesantren-based policies that promote responsible electronic transactions and strengthen financial education in alignment with Islamic values.